Is "efficiency" a useful concept in cognitive neuroscience?. (February 2015) - Poldrack, Russell A.
Highlights: The concept of "efficiency" is often used to describe differences in brain activation between groups or individuals. I argue that this concept is empty and simply redescribes the data. I review different explanations for differences in activation and highlight the challenges in understanding these differences. Abstract: It is common in the cognitive neuroscience literature to explain differences in activation in terms of differences in the "efficiency" of neural function. I argue here that this usage of the concept of efficiency is empty and simply redescribes activation differences rather than providing a useful explanation of them. I examine a number of possible explanations for differential activation in terms of task performance, neuronal computation, neuronal energetics, and network organization. While the concept of "efficiency" is vacuous as it is commonly employed in the neuroimaging literature, an examination of brain development in the context of neural coding, neuroenergetics, and network structure provides a roadmap for future investigation, which is fundamental to an improved understanding of developmental effects and group differences in neuroimaging signals.